Diabetes mellitus, Alter und Komorbiditäten: Ursache für die vielen Pillen = Diabetes mellitus, age and comorbidities : this is why there are so many pills - Bahrmann, Anke (Der Diabetologe, 2017)
Demography and multimorbidityAs a result of demographic developments the number of elderly people in the population is clearly increasing; therefore, a noticeable rise in the proportion of multimorbid elderly people is also to be expected.Effects of guideline recommendationsCurrent guidelines mostly focus only on the respective underlying disease and are not concerned with the problem of multimorbidity in individual cases. Polypharmacy and medication cascades due to undesirable and unrecognized drug-drug interactions are, therefore, not uncommon in the elderly.Pharmaceutical treatment of elderly patientsThe maintenance of health and physical well-being places high demands on pharmacotherapy in the elderly. Polypharmacy is influenced by the number of existing diseases, personal therapy preferences and the treating physician. Undesired drug-drug interactions can lead to an increased tendency to falling, an increase in hospital admissions, an increase in healthcare costs and a reduction in therapy adherence.